Factors contributing to weight gain among students during the COVID-19 pandemic - Marpaung, Jelentika; Marlinang, Putri; Siagian, Masryna; Bangun, Andreas Xaverio; Lister, Gilbert; Deseva, Frisca Gemmi; William, Andy (Buletin Kedokteran & Kesehatan Prima, 2025)
Weight gain among students during the COVID-19 pandemic was largely attributed to lifestyle changes, including diet, sleep patterns, decreased physical activity, and increased gadget use. This study aimed to identify the factors influencing weight gain in students at SMKN 10 Medan. A quantitative methodology was employed, utilizing a cross-sectional approach. The study population consisted of all students at SMKN 10 Medan, totaling 1,108 individuals. A sample of 294 students was selected using a random sampling technique. Data analysis was conducted using the chi-square test and logistic regression. The results indicated that all variables were significantly related to student weight gain during the COVID-19 pandemic, with p-values for physical activity (p=0.036), breakfast habits (p=0.042), snacking habits (p=0.001), sleep patterns (p=0.001), and gadget use (p=0.001). The most influential factors contributing to student weight gain were identified as snacking habits and sleep patterns, which exhibited the lowest significance values. It can be concluded that snacking habits and sleep patterns are the predominant factors associated with weight gain among students at SMKN 10 Medan during the COVID-19 pandemic.